The Influence Of Health Education On The Knowledge And Attitude Of Wus About Early Detection Of Breast Cancer (SADARI) In The Work Area Of Sukaraja Public Health Center, Tasikmalaya Regency - Noorhayati Novayanti; Meti Patimah; Annisa Putri; Hana Nurpadilah (Sean Institute, 2025)
Breast cancer is a severe health problem due to its increasing number (20%) per year, and is the number one cause of death compared to cervical cancer. The prevention and finding of breast cancer at an early stage is an important effort because, in addition to freeing women from the incidence of breast cancer, it suppresses relatively expensive treatment costs. Early detection of breast cancer can be conducted by breast self-examination (SADARI) because by conducting SADARI, it can be recognized whether there is a tumor or abnormality in the breast. SADARI is the most effective and efficient method to detect breast cancer at an early stage. This study aimed to determine the effect of health education on WUS's knowledge and attitudes toward early detection of breast cancer (SADARI). The subjects in this study were WUS (Wanita Usia Subur) in the working area of the Sukaraja Health Center who met the inclusion criteria and by the signing of an informed consent sheet, totaling 30 people with inclusion criteria: not having breast cancer, married, age between 20-40 years. The research method used was a quasi-experiment using a pre-post-test design approach. Research subjects were given an intervention in the form of health education on early detection of breast cancer (SADARI). The results showed an increase in knowledge and attitudes of WUS after being given health education. This study concludes that there is an effect of health education on the knowledge and attitudes of WUS about early detection of breast cancer (SADARI).